Assessment of melatonin level and genetic aspect of type 2 diabetes mellitus patients in Thi-Qar province, Iraq - G. Al-Fartosi, Khalid; A. Jabbar, Enas; A. Jabbar, Ahmed (University of Thi-Qar Journal of Science, 2019)
The present study was designed to assessment of melatonin level and genetic aspects of patients with diabetes mellitus type 2 in Thi-Qar province, Iraq. The sample includes 80 patients compared with 40 as control group. The results showed a significant increase in levels of serum glucose in patients with DM type 2 compared with 40 as a control group at (p<0.05). The level of melatonin showed a significant decrease in patients of diabetes compared with the control group. The genetic study was conducted to identify the potential association of melatonin receptor MTNR1B gene SNPs with the progression of type 2diabetes mellitus (T2DM). In this same locus, four new SNPs were observed and their novelty were proven, including g.10718G>C, g.10863A>G, g.10865G>A, and g.10867T>A, while only one SNP was found to be known, namely rs1431442778. The current results indicated the presence of all of the observed SNPs only in the patients’ samples.